A Review of CAM for Procedural Pain in Infancy: Part II. Other Interventions. Issue 4 (2008) - Tsao, Jennie C. I.; Evans, Subhadra; Meldrum, Marcia; Altman, Tamara; Zeltzer, Lonnie K.
Abstract : This article is the second in a two-part series reviewing the empirical evidence for complementary and alternative medicine (CAM) approaches for the management of pain related to medical procedures in infants up to 6 weeks of age. Part I of this series investigated the effects of sucrose with or without non-nutritive sucking (NNS). The present article examines other CAM interventions for procedural pain including music-based interventions, olfactory stimulation, kangaroo care and swaddling. Computerized databases were searched for relevant studies including prior reviews and primary trials. Preliminary support was revealed for the analgesic effects of the CAM modalities reviewed. However, the overall quality of the evidence for these approaches remains relatively weak. Additional well-designed trials incorporating rigorous methodology are required. Such investigations will assist in the development of evidence-based guidelines on the use of CAM interventions either alone or in concert with conventional approaches to provide safe, reliable analgesia for infant procedural pain.